2016
DOI: 10.1186/s13024-016-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Reactive astrocytes undergo M1 microglia/macrohpages-induced necroptosis in spinal cord injury

Abstract: BackgroundA unique feature of the pathological change after spinal cord injury (SCI) is the progressive enlargement of lesion area, which usually results in cavity formation and is accompanied by reactive astrogliosis and chronic inflammation. Reactive astrocytes line the spinal cavity, walling off the lesion core from the normal spinal tissue, and are thought to play multiple important roles in SCI. The contribution of cell death, particularly the apoptosis of neurons and oligodendrocytes during the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
151
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(162 citation statements)
references
References 56 publications
(67 reference statements)
11
151
0
Order By: Relevance
“…Nec-1 mediates neuroprotective effects in rodent models of acute and chronic neurological conditions, including adult stroke (146), neonatal hypoxia/ischemia (H/I) (147, 148), retinal ischemia (149), retinal detachment (150152), subarachnoid hemorrhage (153, 154), traumatic brain injury (155), spinal cord injury (156159), and amyotrophic lateral sclerosis (160). The ability of Nec-1 to counteract manifestations of amyotrophic lateral sclerosis in mice was backed up by the knockdown of RIPK1 as well as by data obtained using human cells treated with necrosulfonamide (NSA, a chemical that inhibits human MLKL) (160).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nec-1 mediates neuroprotective effects in rodent models of acute and chronic neurological conditions, including adult stroke (146), neonatal hypoxia/ischemia (H/I) (147, 148), retinal ischemia (149), retinal detachment (150152), subarachnoid hemorrhage (153, 154), traumatic brain injury (155), spinal cord injury (156159), and amyotrophic lateral sclerosis (160). The ability of Nec-1 to counteract manifestations of amyotrophic lateral sclerosis in mice was backed up by the knockdown of RIPK1 as well as by data obtained using human cells treated with necrosulfonamide (NSA, a chemical that inhibits human MLKL) (160).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
“…As notable exceptions, Ripk3 −/− mice exhibit an increased resistance to retinal detachment triggered by subretinal injections of sodium hyaluronate (150) or polyI:C (152), as compared with their WT littermates. Similarly, Ripk3 −/− mice exhibit a sizeable reduction in astrocytic demise upon spinal cord injury as compared with WT mice, which correlates with an improved preservation of neurotrophic function (159). Moreover, the administration of a Ripk3 -targeting siRNA limits the demise of outer hair cells exposed to noise that causes a permanent threshold shift in hearing, an otoprotective effect that can be increased by the concomitant administration of Z-VAD-fmk (161).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
“…This is a simple experiment with great clinical significance. Since there is no harm done if the hemostatic drug is carefully chosen, the first thing to do in handling spinal cord injury accidence should be an immediate injection of hemostatic drug, which is particularly important in cases of massive accidents [29,30].…”
Section: Early Hemostasis After Spinal Cord Injurymentioning
confidence: 99%
“…[33,34] Our recent studies demonstrated that RIP3 and phosphorylated MLKL are up-regulated in reactive astrocytes and microglia after SCI. [35,36] Reactive astrocytes, which line the spinal cavity, die by M1 microglia/macrophage induced necroptosis partially through toll like receptor/myeloid differentiation 88 signalling. [35] Microglia, the major player of chronic inflammation post-SCI, die through endoplasmic reticulum stress involved necroptosis.…”
Section: Necroptosis and Neurological Diseasesmentioning
confidence: 99%
“…[35,36] Reactive astrocytes, which line the spinal cavity, die by M1 microglia/macrophage induced necroptosis partially through toll like receptor/myeloid differentiation 88 signalling. [35] Microglia, the major player of chronic inflammation post-SCI, die through endoplasmic reticulum stress involved necroptosis. [36] These researches raised the straightforward question of how necroptosis regulateschronic inflammation after SCI.…”
Section: Necroptosis and Neurological Diseasesmentioning
confidence: 99%